1996
DOI: 10.1021/bi9603579
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Epitope in Antithrombin Appearing on Insertion of the Reactive-Bond Loop into the A β-Sheet

Abstract: Previous work has shown that insertion of the reactive-bond loop of antithrombin into the main beta-sheet of the inhibitor, the A sheet, leads to exposure of epitopes that are not present in intact antithrombin. Identical epitopes are exposed in antithrombin-proteinase complexes, inferring that the reactive-bond loop is inserted into the A beta-sheet also in these complexes. Loop insertion thus presumably is involved in the mechanism of inhibition of target proteinases. In this work, we have identified a linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…However, in contrast to the results presented here on m A b # 2H5, most of these studies were able to precisely determine the linear peptide sequence recognised by the antibodies. For example, Nordling and Bjork (1996) identified a hexapeptide sequence near Helix I of antithrombin that is exposed in all forms of the serpin in which the RCL had been inserted into P-sheet A. Similar to the results presented in this thesis, Picard et al…”
Section: General Discussion and Conclusionsupporting
confidence: 74%
See 2 more Smart Citations
“…However, in contrast to the results presented here on m A b # 2H5, most of these studies were able to precisely determine the linear peptide sequence recognised by the antibodies. For example, Nordling and Bjork (1996) identified a hexapeptide sequence near Helix I of antithrombin that is exposed in all forms of the serpin in which the RCL had been inserted into P-sheet A. Similar to the results presented in this thesis, Picard et al…”
Section: General Discussion and Conclusionsupporting
confidence: 74%
“…These include the proximal and distal hinge regions, F helix, and psheets A and C. Furthermore, several studies have used monoclonal antibodies to investigate the nature of conformational changes associated with the S->R transition in a variety of serpins (eg. PAI-1, antithrombin) (Debrock & Declerck 1995;Nordling & Bjork 1996;Bjorquist et al 1997;Bjorquist et al 1999;Picard et al 1999). These studies used monoclonal antibodies to show the unavailability of epitopes on serpimprotease complexes that were present in the native serpin or appearance of new epitopes on serpin:protease complexes or proteolytically cleaved serpins.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, mouse AT also contains the motif DAFHK and was recognized in immunoblotting, implying that 12A5 was an autoantibody. However, mammalian synthesis of an autoantibody directed against a cryptic region of a self-protein is not implausible; in fact, Nordling and Björk (33) have characterized a rabbit serum that recognizes the sequence VDLFSP shared by rabbit and human AT.…”
Section: A5 a Monoclonal Antibody That Distinguishes At-proteasementioning
confidence: 99%
“…Based on functional studies of serpin variants and immunochemical investigations, a number of reports nevertheless suggest that, in the stable complex, the RCL is inserted into ␤-sheet A. Antibodies have been characterized that fail to react with native serpin, but recognize binary complexes with a synthetic tetradecapeptide corresponding to residues P 14 to P 1 of the RCL, as well as consumed inhibitors (27)(28)(29)(30)(31)(32)(33). Thus, antibodies revealed that insertion of the RCL in ␤-sheet A exposes neoepitopes that are not present in the intact inhibitor.…”
mentioning
confidence: 99%